Observing the interactive qualities of L2 instructional practices in ESL and FSL classrooms - Zuniga, Michael; Simard, Daphnée (Studies in Second Language Learning and Teaching, 2016)
Discourse features that promote the generation of interactionally modified input and output, such as negotiation for meaning, have been shown to significantly enhance second language acquisition. Research has also identified several characteristics of instructional practices that render them more or less propitious to the generation of these discourse features. While various classroom observation studies have successfully measured the communicative orientation of classroom environments, most of the indicators of interactivity analyzed in those studies were obtained through micro-level discourse analyses and not through macro-level analyses of task-related factors shown to directly influence the interactivity of instructional practices. Such a macro-level scale has potential practical implications for teachers and administrators seeking an efficient tool for assessing and improving the interactivity afforded by a given curriculum. The objective of the present study was therefore to develop macro-level scale to determine the extent to which teachers of French and English as a second language use interaction-friendly instructional practices. Using an observation scheme designed to code data on factors shown to influence interactivity, 63 hours of FSL and ESL classes from secondary schools in the Montreal area were observed and analyzed. Results indicate clear differences between the two groups. While both ESL and FSL classes were less teacher-centered than those observed in previous studies, they were still rated as not-very-interactive. Target language differences showed that the FSL classes were more teacher-centered and characterized by fewer interaction-friendly tasks and activities than the ESL classes. Task characteristics, reasons for ESL and FSL differences and recommendations for improvement are discussed.